2010
DOI: 10.1038/nature09126
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal control of the shoot stem-cell niche

Abstract: The classic phytohormones cytokinin and auxin play essential roles in the maintenance of stem-cell systems embedded in shoot and root meristems, and exhibit complex functional interactions. Here we show that the activity of both hormones directly converges on the promoters of two A-type ARABIDOPSIS RESPONSE REGULATOR (ARR) genes, ARR7 and ARR15, which are negative regulators of cytokinin signalling and have important meristematic functions. Whereas ARR7 and ARR15 expression in the shoot apical meristem (SAM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
410
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(433 citation statements)
references
References 31 publications
19
410
1
3
Order By: Relevance
“…The phytohormone cytokinin (CK) is an important factor for shoot meristem maintenance and organ positioning (37)(38)(39)(40). Auxin has been implicated in the regulation of CLV3 through CK signaling, suggesting that auxin homeostasis in the SAM is important to control stem cell fate (40).…”
Section: Discussionmentioning
confidence: 99%
“…The phytohormone cytokinin (CK) is an important factor for shoot meristem maintenance and organ positioning (37)(38)(39)(40). Auxin has been implicated in the regulation of CLV3 through CK signaling, suggesting that auxin homeostasis in the SAM is important to control stem cell fate (40).…”
Section: Discussionmentioning
confidence: 99%
“…Following these criteria, a subset of eight genes was identified that encoded proteins controlling transcription ( Figure 2). Since these genes are known to function in the specification of floral organs (Kunst et al, 1989;Weigel et al, 1992;Rashotte et al, 2006;Zhao et al, 2010), it appears that IAA modulation of ETT activities is particularly important in spatio-temporal regulation of floral tissue identity and differentiation.…”
Section: Ett Regulates a Subset Of Its Targets In An Iaa-sensitive Mamentioning
confidence: 99%
“…To determine the roles of ARR in the regeneration of shoots in callus on SIM, the transcription of ARR1, ARR10, and ARR12 needs to be temporally repressed. For this purpose, we used artificial microRNAs (am) driven by an ethanol-inducible promoter to silence the transcripts of ARR1, ARR1/10, ARR1/12, ARR10/12, or ARR1/ 10/12 (am-ARR1, am-ARR1/10, am-ARR1/12, am-ARR10/12, and am-ARR1/10/12, respectively) (Leibfried et al, 2005;Zhao et al, 2010). The efficiency and specification of these artificial microRNAs were tested by real-time PCR.…”
Section: Reestablishment Of Shoot Meristem Requires the Function Of Amentioning
confidence: 99%
“…Artificial microRNAs targeting ARR1, ARR1/10, ARR10/12, and ARR1/10/ 12 were designed using the WMD3-Designer and were cloned into an ethanol-inducible vector (Leibfried et al, 2005;Zhao et al, 2010) to produce the ProAlcA:am-ARR1, ProAlcA:am-ARR1/10, ProAlcA:am-ARR1/12, ProAlcA:am-ARR10/12, and ProAlcA:am-ARR1/10/12 constructs. A genomic fragment of 4597 bp containing a 2527-bp sequence upstream of the ATG start codon and the coding region without the stop codon of ARR1 was amplified by PCR from Arabidopsis genomic DNA with the primers pARR1-genomic-F, pARR1-genomic-R, ARR1-cDNA-F, and ARR1-cDNA-R and was recombined into pROKII-GFP to generate the ProARR1:ARR1-GFP expression vector.…”
Section: Plasmid Construction and Plant Transformationmentioning
confidence: 99%